Synthesis and Spectral Analysis of Novel Substituted Benzimidazole Derivatives - Jadhav, Bhagyashri D.; Narkhede, Sushil Prabhakar (International Journal of Pharmaceutical Investigation, 2025)
Aim The aim of the present study is to synthesize novel series of substituted benzimidazole derivatives and their spectral characterization. Materials and Methods This study presents research on the synthesis of novel series of substituted benzimidazole derivatives using primary amine as the starting compound. Results All synthesized compounds were analyzed using 1 hydrogen nuclear magnetic resonance, Fourier transform infrared and mass spectrometry to validate their structures. Conclusion Overall, the exploration of substituted benzimidazole derivatives with varied functional groups as potential candidates for further advancement as therapeutic agents.
Keywords: 2-(2 Chloro Phenyl)-1H Benzimidazole; Amine; Primary; Substituted